1997
DOI: 10.1038/sj.ejcn.1600463
|View full text |Cite
|
Sign up to set email alerts
|

Body fatness and bioelectrical impedance in non-obese pre-menarcheal girls: comparison to anthropometry and evaluation of predictive equations

Abstract: Objectives: To determine in non-obese pre-menarcheal girls if bioelectrical impedance (BIA) is a better predictor of body fatness than triceps skinfold (TSF) or body mass index (BMI) and to cross-validate published equations for determination of fat-free mass (FFM) from BIA in pre-menarcheal girls. Design: Cross-sectional analysis of data from 132 non-obese pre-menarcheal girls. The relationship of percent body fat (%BF), derived from isotopic dilution of H 2 18 O to TSF, BMI, and %BF by BIA, calculated from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Mineral deposition was apparent over the age range we studied and is believed to be completed in early adulthood (31). FFM hydration was significantly higher than in adults; however, although previous work has shown similar results (32,33), investigators continue to use adult-derived values in 2C models used to study children (36). The ratio of mineral to protein also differed significantly by Ϸ20% from that in adults, but the magnitude of this difference was not sufficient to cause error when the adult value was used in combination with a 3C model to estimate hydration and density of FFM.…”
Section: Discussionmentioning
confidence: 74%
“…Mineral deposition was apparent over the age range we studied and is believed to be completed in early adulthood (31). FFM hydration was significantly higher than in adults; however, although previous work has shown similar results (32,33), investigators continue to use adult-derived values in 2C models used to study children (36). The ratio of mineral to protein also differed significantly by Ϸ20% from that in adults, but the magnitude of this difference was not sufficient to cause error when the adult value was used in combination with a 3C model to estimate hydration and density of FFM.…”
Section: Discussionmentioning
confidence: 74%
“…It has been recommended that an equation be validated on each different BIA analyser and for each population in which it is to be used. 4,12,20 When considering validation of BIA it is important to understand the statistical methods used. Many authors only report the correlation between BIA and the reference method and this can be misleading as it does not test the equivalence of the results given by the different methods.…”
Section: Discussionmentioning
confidence: 99%
“…4 ± 12 The few studies that have examined its ability to predict percentage body fat (PBF) found that BIA was superior to BMI and that BIA was similar to SFT performed by trained observers. 4,5,13,14 BIA is painless, requires less training and is subject to less interobserver variation than SFT measurement. 6 Conventional BIA requires careful placement of electrodes on the arm and leg.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, differences in the proportion of these components might be masked by BMI, which is dependent on weight and height. Bandini et al 16 have also reported a low accuracy of BMI compared with skinfolds when estimating fatness in pre-pubertal children.…”
Section: Discussionmentioning
confidence: 99%